Acute bacterial skin and soft tissue infections: new drugs in ID armamentarium - Tirupathi, Raghavendra (J Community Hosp Intern Med Perspect, 2019)
Acute bacterial skin and soft tissue infections (SSTI) are among the most common reasons for hospitalization of adults in the USA today. Cellulitis or SSTI can cause significant morbidity and mortality. The 2014 IDSA guideline update for the management of skin and soft tissue infections classified skin infections as purulent cellulitis (causative pathogen – Staphylococcus aureus including MRSA) and nonpurulent cellulitis (causative pathogens include Streptococcus). Understanding the key difference and categorization will allow a physician to determine the appropriate treatment approach and antibiotic choice. In recent years, there have been several new antibiotics which received fast track approval by FDA as a Qualified Infectious Disease Product (QIDP) for the indication of SSTI. They Include Ceftaroline (Teflaro), Dalbavancin (Dalvance), Oritavancin (orbativ), Tedizolid (Sevixtro), Delafloxacin (Baxdela) and Omadacycline (Nuzyra). This article will briefly review each of these new antibiotics and summarize their roles in avoiding hospital admissions and reducing the duration of stay in patients with SSTI.